2017
DOI: 10.1126/science.aaf0683
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of exhausted CD8 T cells by PD-1–targeted therapies is CD28-dependent

Abstract: Programmed cell death-1 (PD-1) targeted therapies enhance T cell responses and show efficacy in multiple cancers but the role of costimulatory molecules in this T cell rescue remains elusive. Here we demonstrate that the CD28/B7 costimulatory pathway is essential for effective PD-1 therapy during chronic viral infection of mice. Conditional gene deletion showed a cell-intrinsic requirement of CD28 for CD8 T cell proliferation after PD-1 blockade. B7-costimulation was also necessary for effective PD-1 therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
689
5
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 818 publications
(740 citation statements)
references
References 29 publications
42
689
5
4
Order By: Relevance
“…Both PD-1 and CD28 preferentially co-cluster to provide a mechanism by which these co-receptors interact for de-phosphorylation. Consistent with this, others have shown that PD-1 blockade requires the expression of CD28 for the recovery of exhausted T cell responses [48] . The interplay involving CTLA-4 and PD-1 with CD28 may be indicative of a general theme of interplay between members of the CD28 family in the regulation of T-cell responses.…”
Section: Immunotherapysupporting
confidence: 60%
See 1 more Smart Citation
“…Both PD-1 and CD28 preferentially co-cluster to provide a mechanism by which these co-receptors interact for de-phosphorylation. Consistent with this, others have shown that PD-1 blockade requires the expression of CD28 for the recovery of exhausted T cell responses [48] . The interplay involving CTLA-4 and PD-1 with CD28 may be indicative of a general theme of interplay between members of the CD28 family in the regulation of T-cell responses.…”
Section: Immunotherapysupporting
confidence: 60%
“…CTLA-4) mice depend on CD28 expression [46] . More recently, two new papers have shown that PD-1 operates via inhibition of CD28 signaling [47,48,49] . PD-1 associates with SHP-2 which preferentially dephosphorylates CD28 (Figure 1B).…”
Section: Immunotherapymentioning
confidence: 99%
“…PD-1 expression on tumorinfiltrating CD8 þ T cells correlates with impaired effector cell function (2,11), while PD-L1 expression on tumors can facilitate escape from the host immune system (3) and can serve as a prognostic factor (12). Recent evidence indicates that recovery of responses from anti-PD-1 blockade depends on the related coreceptor (13)(14)(15). The nature of the intracellular signaling pathways that regulate PD-1 expression on T cells has been the subject of much interest.…”
Section: Introductionmentioning
confidence: 99%
“…Current checkpoint inhibitor therapies act by reinforcement of pre-existing T cell anti-tumour responses and are therefore most effective in inflamed tumours. In the presence of an active T cell tumour response, IFN-γ produced by T cells and other immune cells upregulate the expression of PD-L1, which counters T cell receptor and CD28-mediated activation signals of T cells (Hui et al 2017, Kamphorst et al 2017. In clinical studies of PD-1 or PD-L1 antagonists, high T cell density and the adaptive increase of PD-L1 expression on tumour and immune cells are often used as features of an active anti-tumour T cell response (Chen & Mellman 2017).…”
Section: :12mentioning
confidence: 99%